The fluid voter: Exploring independent voting patterns over time. Issue 1 (23rd January 2023) - Reilly, Thom; Hunting, Dan
Abstract: Independents remain hard to categorize because they are, by their choice of self‐identification, resisting the standard categories of political classification. Despite the growth in independent voter identity, many political strategists still view independents as partisans. In this article, we contribute to the academic literature on independent voting behavior by exploring whether those who identify as politically independent function as true independents by accounting for their voting patterns over time. We do this by analyzing data produced by the American National Election Studies (ANES) on political identification and voting choices from 1972 to 2020 on each of the three ANES measures of party affiliation. Our findings show when tracking independent voting behavior over more than one election, there is a significant volatility in voting loyalty and independents as a group are distinct from partisans. This volatility was observed in all three measures of party affiliation used by the ANES survey data. The research also finds evidence that a sizeable number of independents move in and out of independent status from one election to another. Related Articles: Grossmann, Matt. 2014. "The Varied Effects of Policy Cues on Partisan Opinions." Politics & Policy 42(6): 881–904. https://doi.org/10.1111/polp.12102 . Reilly, Thom, and E. C. Hedberg. 2022. "Social Networks of Independents and Partisans: Are Independents a Moderating Forcer?" Politics & Policy 50(2): 225–43. https://doi.org/10.1111/polp.12460 . Saeki, Manabu. 2019. "Anatomy of Party Sorting: Partisan Polarization of Voters and Party Switching." Politics & Policy 47(4): 699–747. https://doi.org/10.1111/polp.12318 . El votante fluido: exploración de patrones de votación independientes a lo largo del tiempo: Los independientes siguen siendo difíciles de categorizar porque, por su elección de autoidentificación, se resisten a las categorías estándar de clasificación política. A pesar del crecimiento de la identidad de los votantes independientes, muchos estrategas políticos todavía ven a los independientes como partidistas. En este artículo, contribuimos a la literatura académica sobre el comportamiento del voto independiente al explorar si aquellos que se identifican como políticamente independientes funcionan como verdaderos independientes al dar cuenta de sus patrones de voto a lo largo del tiempo. Hacemos esto analizando los datos producidos por los Estudios Electorales Nacionales Estadounidenses (ANES) sobre la identificación política y las opciones de votación desde 1972 hasta 2020 en cada una de las tres medidas de afiliación partidaria de ANES. Nuestros hallazgos muestran que cuando se rastrea el comportamiento de los votantes independientes en más de una elección, existe una volatilidad significativa en la lealtad al voto y los independientes como grupo son distintos de los partidistas. Esta volatilidad se observó en las tres medidas de afiliación partidaria utilizadas por los datos de la encuesta ANES. La investigación también encuentra evidencia de que un número considerable de independientes entran y salen del estado independiente de una elección a otra. 易变的选民:探究随时间推移的独立投票模式: 独立人士仍然是难以归类的，因为他们根据其对自我身份识别的选择，抵制政治分类的标准类别。尽管独立选民身份出现增长，许多政治战略家仍然将独立选民视为党派人士。本文中，我们通过解释自认为政治独立的人随时间推移的投票模式，探究其是否发挥了真正的独立人士作用，进而为关于独立投票行为的学术文献作贡献。为此，我们以美国国家选举研究(ANES)对党派性的三种衡量标准，分析了1972至2020年间ANES的政治认同和投票选择数据。我们的研究结果表明，在追踪不止一次选举的独立投票行为时，投票忠诚度存在显著波动，并且独立人士群体与党派人士截然不同。在ANES调查数据使用的三种党派性衡量标准中都观察到了这种波动。本研究还发现，有相当数量的独立人士在不同选举中表现或不表现其独立身份。